A Feasibility study on SunIce ice plant powered by alternative energy - Abis, Sabrina Marie K.; Bongat, Jejomar O.; Cucio, Adriel Jireh V.; Madredia, Maila Rae O. (College of Engineering, 2013)
This feasibility study on the establishment of an ice plant powered by alternative energy, aptly named Sunice, is conducted to explore and develop the potential of the utilization of solar energy to power manufacturing facilities that are especially dependent on electricity to produce their main product. In the context of this study, solar energy is used to power an ice plant in Tabaco City, Albay, where the cost of electricity in the said province is considerably higher than the rest of Luzon. The study consists of three major parts, assessing feasibility in the aspects of the Market, Technology and Finance. An investment proposal is also made to synthesize the findings of the study, and to encourage potential investors to participate in the start-up of the enterprise. The Market Study establishes the presence of the demand for the product, particularly in the fishing industry which is strongly present and stable in Tabaco City. The study has established that the company can supply its products across all points of the fishing industry's supply chain. The study has also established consumer behavior, which has been determined to be highly dependent on product price more than anything else. The study has established that product should ideally be offered primarily to deep sea fishermen, fish vendors, restaurants, and fish dealers. The Technical Study describes and analyzes the several aspects of the establishment of an ice plant. The study investigates the equipment, machinery, tooling, and materials required to run such facility. Moreover, the study also determines the compatibility and the feasibility of using solar energy to power the facility. The study also determined the additional investment cost that is entailed by the acquisition of solar photovoltaic arrays and other related equipment, as well as the annual savings that are used by such. It has then been determined that this additional investment will be recovered within 7 years, assuming that only the avoided cost of electricity will be used in determining the recovery period. This avoided cost, however, will continue to be realized even after the recovery of the additional investment. Finally, the financial feasibility study considers the sourcing of funds, the total project costs, projected revenues as well as cash flows of the project. Tools such as the Net Present Value and Internal Rate of Return analysis were utilized, and this yielded that the Net Present Value of the proposed enterprise is at PhP 19,001,212.45, with an Internal Rate of Return of 46.65% over 10 years, with a Minimum Acceptable Rate of Return of 10.0%. Financial statements were also determined, and this has led to the conclusion that the establishment and operation of Sunice is not only feasible but also profitable.